A noise-resistant signal-code generation algorithm based on the nonlinear system with cross feedback for secure telecommunications systems - Dubrovsky, V. V.; Popova, M. S. (2018Systems of Signal Synchronization, Generating and Processing in Telecommunications (SYNCHROINFO), 2018)
The algorithm of generation of pseudo-random sequences generated at the output of a nonlinear system with cross feedbacks and time-varying parameters is considered in the article. The results of numerical modeling on the estimation of the lateral emissions of normalized autocorrelation sequence functions are presented, as well as the character of the distribution of their reference values. The structural-functional scheme of the generation device is given and the ways of practical realization are indicated. A method of information modulation and demodulation of a useful signal against the background of additive interference is proposed.